2016
DOI: 10.1515/intag-2015-0083
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical models for prediction of rheological parameters in vinasses derived from sugar cane

Abstract: A b s t r a c t. The rheological behaviour of vinasses derived from sugar cane was studied as a function of time (0 and 600 s), soluble solids content (44 and 60 °Brix), temperature (10 and 50°C), and shear rate (0.33 and 1.0 s -1 ). The results indicated that vinasses were time-independent at 25°C, where shear stress values ranged between 0.01 and 0.08 Pa. Flow curves showed a shear-thinning rheological behaviour in vinasses with a flow behaviour index between 0.69 and 0.89, for temperature between 10 and 20°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
1
Order By: Relevance
“…The power-law model parameters (consistency index and power-law index) are presented in the Table 3. In contrast to the previous study [35], the consistency index and the power-law index increase with the increase of temperature [53]. At 40°C, the temperature closest to the mesophilic regime, the power-law index is 1.01, characterizing Newtonian behavior.…”
Section: Rheological Behavior Of Wastewatercontrasting
confidence: 92%
See 1 more Smart Citation
“…The power-law model parameters (consistency index and power-law index) are presented in the Table 3. In contrast to the previous study [35], the consistency index and the power-law index increase with the increase of temperature [53]. At 40°C, the temperature closest to the mesophilic regime, the power-law index is 1.01, characterizing Newtonian behavior.…”
Section: Rheological Behavior Of Wastewatercontrasting
confidence: 92%
“…In a study conducted by Chacua et al (2016), it has been shown that vinasse has a pseudoplastic behavior for temperatures between 10 and 20 °C [53]. Indeed, when the temperature is superior to 30 °C, the power-law index is close to 1, indicating an approach to the Newtonian model [53].…”
Section: Rheological Behavior Of Wastewatermentioning
confidence: 97%